Tìm giá trị nguyên của n để A chia hết B
A = x2y3 + 2x3y2 - x2y2 và B = xnyn
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
6a( x - 3y ) - 8b( 3y - x )
= 6a( x - 3y ) + 8b( x - 3y )
= 2( x - 3y )( 3a + 4b )
\(6a\left(x-3y\right)-8b\left(3y-x\right)\)
\(=6a\left(x-3y\right)+8b\left(x-3y\right)\)
\(=\left(6a+8b\right)\left(x-3y\right)=2\left(3a+4b\right)\left(x-3y\right)\)
\(\left(2x+1\right)^2+\left(4x-2\right)^2-3\left(2x+1\right)\left(4x-2\right)\)
\(=4x^2+4x+1+16x^2-16x+4-6\left(2x+1\right)\left(2x-1\right)\)
\(=20x^2-12x+5-6\left(4x^2-1\right)\)
\(=20x^2-12x+5-24x^2+6=-4x^2-12+11\)
\(\frac{x^2+3x}{x^2+6x+9}+\frac{3}{x-3}+\frac{6x}{9-x^2}\)
ĐKXĐ : x ≠ ±3
\(=\frac{x\left(x+3\right)}{\left(x+3\right)^2}+\frac{3}{x-3}-\frac{6x}{x^2-9}\)
\(=\frac{x}{x+3}+\frac{3}{x-3}-\frac{6x}{\left(x-3\right)\left(x+3\right)}\)
\(=\frac{x\left(x-3\right)}{\left(x-3\right)\left(x+3\right)}+\frac{3\left(x+3\right)}{\left(x-3\right)\left(x+3\right)}-\frac{6x}{\left(x-3\right)\left(x+3\right)}\)
\(=\frac{x^2-3x}{\left(x-3\right)\left(x+3\right)}+\frac{3x+9}{\left(x-3\right)\left(x+3\right)}-\frac{6x}{\left(x-3\right)\left(x+3\right)}\)
\(=\frac{x^2-3x+3x+9-6x}{\left(x-3\right)\left(x+3\right)}\)
\(=\frac{x^2-6x+9}{\left(x-3\right)\left(x+3\right)}\)
\(=\frac{\left(x-3\right)^2}{\left(x-3\right)\left(x+3\right)}=\frac{x-3}{x+3}\)
n={1;2;3}